Fanon and Recognition: Finding Hegelian Self-Consciousness Through Struggle - Visscher, Peter (Stance: an international undergraduate philosophy journal, 2020)
This paper applies Hegel’s master-slave dialectic to Fanon’s issue of pseudo-recognition discussed in the essay, “The Negro and Recognition,” as a way of establishing a form of self-consciousness. I begin the paper by arguing that in the Hegelian dialectic establishing a self-consciousness is an essential prerequisite to Fanon’s goal of mutual subject-recognition. I then argue that given the position of black people as slaves within the master-slave dialectic, they are denied the recognition required to attain being in-itself for-itself, which in reality can only be obtained if black people establish self-consciousness on their own terms. I then make the case that this required self- consciousness can only be obtained through struggle, essentially reversing the stages of the dialectic to create a new master/slave relation. In particular, I argue that this moment of struggle provides a moment of proto-recognition which can be used to build a new mutual subject-recognition. I then theorize on what form this new relation must take, making the case that it must be a relation where the categories of master and slave are made irrelevant, and where all subjects are capable of mutual recognition.